Graphene oxide membranes for electrochemical energy storage and conversion. (25th January 2018) - Eftekhari, Ali; Shulga, Yury M.; Baskakov, Sergey A.; Gutsev, Gennady L.
Abstract: Graphene oxide (GO) membranes have recently attracted considerable attention for various applications involving filtration. In electrochemical systems, GO membranes serve as a separator or solid-state electrolyte; the roles which have been played for over four decades by the commercial ionic polymers such as Nafion. Owing to the versatility of GO membranes, they have shown an incredible potential for electrochemical energy storage and conversion. In lithium-sulphur batteries and similar electrochemical systems in which the electrode redox system is based on a conversion mechanism and subject to the so-called shuttle effect, a selective membrane can facilitate the transport of the electroactive species such as Li ions while blocking the release of the electroactive material ( e.g., polysulphides) into the other half-cell. The same requirement is essential for the fabrication of redox flow batteries. Owing to the growing interest in flexible supercapacitors, there is a desire to replace liquid electrolytes with solid electrolytes, and GO membrane provides an appropriate scaffold for trapping gel electrolytes. The performance of Nafion in fuel cells has also been improved by the preparation of GO/Nafion membranes. All these different applications reveal the practical potential of GO membranes for the future energy storage and conversion. Graphical abstract: Highlights: The similarity of graphene oxide membrane performance for electrochemical energy storage and conversion is reviewed. The advantages of graphene oxide over commercial ionic polymers such as Nafion are discussed. The roles of graphene oxide membranes as solid electrolyte or separators are summarized.